Monitoring and control of power preparedness of athletes in flatwater rowing and canoeing using strain gauges - Alooeff, E.; Guseinov, D.; Lukashevich, D.; Bykov, D.; Minchenya, A. (Proceedings of the 12th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2024)
Control over the preparedness of flatwater rowers and canoeists is realized in the process of solving a variety of particular problems related to the organization of training activities, planning and dosing of loads, selection of training tools and methods for assessing various aspects of readiness and competent interpretation of the results obtained for carrying out corrective measures. Solving these problems is facilitated by strain gauges, which make it possible to record dynamic and some kinetic parameters in natural rowing conditions (on water recording) as part of training and monitoring activities. The article presents the developed strain gauge sensors, describes the features of their calibration and mounting on an athlete`s paddle, and also proposes software for automated processing of recorded data. The article is based on a practice-oriented study on experimental testing of the developed sensors as part of the training and monitoring process.